Schaum's out lines of theory and problems of numerical analysis, 2nd edition - Scheid Francis (Tata McGraw hill, New delhi, 2004)
Stats/Maths
ENGLISH
Keywords: Schaum's out lines of theory and problems of numerical analysis, 2nd edition; Stats/Maths; Stats/Maths